Development of perfusable organ-on-chip with curved microchannel - Tan, Sakina Jin Swan (Nanyang Technological University, 2021)
Organ-on-chips are microfluidic-based platforms which provide well-controlled biophysical microenvironment for complex 3D cell cultures. They are often used for drug development and disease modelling due to better physiological relevance with in vivo conditions. Vascular organ-on-chip is of huge interest due to its potential in providing more accurate preclinical drug testing and for understanding disease mechanism. While several vascular organ-on-chip platforms have been reported, there are still limited studies that construct multi-layered arterial wall structure, and with relevant vessel geometries (e.g., circular lumen) for perfusion studies. In this study, we used a surface tension-based approach to pattern hydrogel in curved microchannels to create a 3D multi-layered structure desired for vascular organ-on-chip applications. Different device dimensions and fabrication methods were first tested to achieve optimal hydrogel patterning and perfusion cell culture. Our results showed that microchannel width larger or equal to 1 millimetre could successfully confine the hydrogel without overflowing to adjacent channels. Next, we developed a novel experimental setup for perfusion cell culture using the vascular-on-chip device and demonstrated successful perfusion at a flow rate of 10 mL/min without gel breakage. Future work includes optimization to induce higher shear stresses on the lumen to match physiological conditions in human arteries.